Quality of a Supporting Mobile App for Rheumatic Patients: Patient-Based Assessment Using the User Version of the Mobile Application Scale (uMARS) - Lambrecht, Antonia; Vuillerme, Nicolas; Raab, Christina; Simon, David; Messner, Eva-Maria; Hagen, Melanie; Bayat, Sara; Kleyer, Arnd; Aubourg, Timothee; Schett, Georg; Hueber, Axel; Knitza, Johannes (Frontiers in Medicine, 2021)
Introduction: Mobile applications promise to improve current health care. However, current mobile app quality ratings are mostly physician-based. The aim of this study was (1) to assess the quality of the self-management app Rheuma Auszeit using the validated uMARS (User Version of the Mobile App Rating Scale) app quality assessment tool and (2) to evaluate the association between uMARS scores and patients' characteristics.
CRIS-Team WoS Importer:2021-08-20